To Believe or Not to Believe in Absolute Monotheism (Tawhid) is a Personal Choice with Consequences: Binary Messages in Quran’s Verses on Iman and Shahada - Saleh Muhammad Harunur Rashid Khan (Al-Bayan: Jurnal Studi Al-Qur'an dan Tafsir, 2025)
The main objective of this article is to interpret a recurring binary message of divine rewards and retributions in two sets of verses about Iman and Shahada. We employ a stratified sampling procedure for retrieving 139 verses on Iman and 44 verses on Shahada from the Quran SmartSearch database available on the islamicity.org website. The research methodology encompasses: (a) content analysis—primarily frequency counts—of original Arabic terms related to Iman and Shahada, and (b) context analysis of selected themes in samples drawn from passages of three or more verses. This study finds that Iman and Shahada are linked through the doctrine of Absolute Monotheism (Tawhid), but they differ in the frequency and nature of binary messages. Compared to significantly higher frequencies of Iman verses, fewer Shahada verses display greater varieties of semantics, derived from their triliteral root (TRS). Shahada verses emphasise testimony to tawhid over binary themes of reward and punishment, whereas Iman verses use simpler language and display greater emphasis on binary messages. Although there is extensive literature on Iman and Shahada, this article offers a new perspective on understanding the nuanced relationship between them. This research contributes a reproducible framework for Quranic thematic studies by combining quantitative frequency analysis with qualitative context interpretation. Substantively, it highlights Shahada's semantic richness for tawhid-centered activities and Iman's straightforward binary messaging, providing hermeneutic insights for fiqh, interfaith dialogue, and gender-/disability-inclusive community empowerment.